ANALISIS PENGARUH PEMULIHAN PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA HOTEL TJAMPUHAN UBUD - Surya Adhitya, Cok Raka; Bayu Rahanatha, Gede (E-Jurnal Manajemen, 2015)
This study aims to: Determine the influence of procedural justice on customer satisfaction Tjampuhan Ubud. Determine the influence of interactional justice on customer satisfaction Tjampuhan Ubud. Determine the influence of distributive justice on customer satisfaction Tjampuhan Ubud. This study used 75 samples, the method of collecting data through questionnaires, the study documentation and observation. Data analysis was performed with multiple linear regression analysis. The results showed: Justice procedural and significant positive effect on customer satisfaction, as evidenced by the t-test value of 3.950> t-table amounted to 1,993, with a significance level of 0.000 <0.05. Interactional Justice and significant positive effect on customer satisfaction, this is evidenced by the value of 2,310 t count> t-table amounted to 1,993, with a significance level of 0.024 <0.05. Distributive justice positive and significant impact on customer satisfaction, this is evidenced by the value of 3.13 t count> t-table amounted to 1,993, with a significance level of 0.002 <0.05.
Keywords: Recovery Services, Procedural Justice, Distributive Justice and Interactional Justice Customer Satisfaction